(untitled) (Journal of Health, Population and Nutrition, 2010)
In-house contamination of drinking-water is a persistent problem in developing countries. This study aimed at identifying critical points of contamination and determining the extent of recontamination after water treatment. In total, 81 households were visited, and 347 water samples from their current sources of water, transport vessels, treated water, and drinking vessels were analyzed. The quality of water was assessed using Escherichia coli as an indicator for faecal contamination. The concentration of E. coli increased significantly from the water source [median=0 colony-forming unit (CFU)/100 mL, interquartile range (IQR: 0-13)] to the drinking cup (median=8 CFU/100 mL; IQR: 0-550; n=81, z=-3.7, p<0.001). About two-thirds (34/52) of drinking vessels were contaminated with E. coli. Although boiling and solar disinfection of water (SODIS) improved the quality of drinking-water (median=0 CFU/100 mL; IQR: 0-0.05), recontamination at the point-of-consumption significantly reduced the quality of water in the cups (median=8, IQR: 0-500; n=45, z=-2.4, p=0.015). Home-based interventions in disinfection of water may not guarantee health benefits without complementary hygiene education due to the risk of post-treatment contamination. Key words: Disinfection; Drinking-water; Hygiene; Water management; Water pollution; Water supply; Bolivia DOI: 10.3329/jhpn.v28i1.4521 J Health Popul Nutr 2010 Feb; 28(1): 34-41